A rare primary pulmonary tumor of childhood - (:unkn) unknown (TURKISH J PEDIATRICS, 2002)
Pleuropulmonary blastoma (PPB) is known to be the pulmonary blastoma of childhood. it has a range of macroscopic and microscopic features which appear to correlate with eventual Prognosis. Type 1, presenting as a multicystic lesion, occurs at an earlier age and has a more favorable prognosis than other types. The presented case of type I PPB had a microscopic focus of rhabdomyosarcoma. Although this patient was disease-free one year after the initial diagnosis without chemotherapy, he presented at 14 months with local dissemination and cardiac metastasis, revealing the inevitable chemo-radiotherapy need in PPB.
Keywords: blastomas; childhood tumors; histopathology; pleuropulmonary blastoma; prognostic factors; PLEUROPULMONARY BLASTOMA; RHABDOMYOSARCOMA; MALIGNANCIES; CHILDREN; CYSTS; LUNG